Intercrossed analysis of the evaluative conceptions of teachers and students of Chemistry of State Public High Schools in the period of the Covid-19 Pandemic (2019/2021) in the Municipality of Codó-MA (Research, Society and Development, 2022)
The evaluation process is one of the fundamental stages of didactic activity in the construction of teaching work, in formal and non-formal spaces. In this view, the related research portrays, as a central objective, about the evaluation methods and instruments from an intercrossed analysis of the evaluative conceptions of Chemistry teachers, comprising, as a differential, the pandemic period (2019/2021) and Emergency Remote Teaching of the teachers of the State Public Schools of Secondary Education of the Municipality of Codó-MA. Methodologically, the use of observational and comparative methods was used in order to apply a correlation with praxis, contributing to a reflection by teachers and analyzing how the instruments used contribute or disadvantage students' learning in the light of the authors' conceptions of the evaluation. of learning. The results showed that most teachers, in addition to having misconceptions, are "stuck" to a quantitative perspective and still find it difficult to evaluate qualitatively because they are inserted in a system that prioritizes quantitative and short-term results.